2020
DOI: 10.3389/fphys.2019.01595
|View full text |Cite
|
Sign up to set email alerts
|

HMGB1 Protects the Heart Against Ischemia–Reperfusion Injury via PI3K/AkT Pathway-Mediated Upregulation of VEGF Expression

Abstract: Delivery of exogenous high mobility group box 1 (HMGB1) may exert a beneficial effect on myocardial ischemia-reperfusion (I/R) injury. Since the expression of vascular endothelial growth factor (VEGF) and phosphatidylinositol 3-kinase/protein kinase B (PI3K/Akt) in the myocardium mediates the cardioprotective function of basic fibroblast growth factor, we hypothesized that VEGF and the PI3K/Akt signaling pathway also mediate the protective effects of intravenously delivered HMGB1. Thus, the objective of the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 49 publications
0
23
0
Order By: Relevance
“…We recently found that post-ischemic AKT levels and phosphorylation are unaltered by IPC or T2D [44], leaving the possibility that phosphorylation patterns during the IPC stimulus and/or initial minutes of reperfusion might be modified with ALA; AKT phosphorylation at these times is linked to I-R outcomes and cardioprotection. Shifts in select inflammatory mediators and VEGF could participate in improved IPC with ALA, while excess TNF-α and HMGB1 are both linked to myocardial injury; TNF-α signaling is also implicated in cardiac preconditioning [131] and HMGB1 may additionally precondition hearts via up-regulating protective VEGF [132], which was augmented by ALA here. Finally, it is also notable that n-3 PUFAs are highly pleiotropic [133], and could influence IPC through cytochrome P450 (e.g., epoxyeicosanoid formation) and arachidonate metabolic pathways [134], inter-related endocannabinoid signaling [135], activation of key transcriptional regulators [136], and/or inhibition of oxidative stress [137].…”
Section: Inflammatory Mediatorsmentioning
confidence: 75%
“…We recently found that post-ischemic AKT levels and phosphorylation are unaltered by IPC or T2D [44], leaving the possibility that phosphorylation patterns during the IPC stimulus and/or initial minutes of reperfusion might be modified with ALA; AKT phosphorylation at these times is linked to I-R outcomes and cardioprotection. Shifts in select inflammatory mediators and VEGF could participate in improved IPC with ALA, while excess TNF-α and HMGB1 are both linked to myocardial injury; TNF-α signaling is also implicated in cardiac preconditioning [131] and HMGB1 may additionally precondition hearts via up-regulating protective VEGF [132], which was augmented by ALA here. Finally, it is also notable that n-3 PUFAs are highly pleiotropic [133], and could influence IPC through cytochrome P450 (e.g., epoxyeicosanoid formation) and arachidonate metabolic pathways [134], inter-related endocannabinoid signaling [135], activation of key transcriptional regulators [136], and/or inhibition of oxidative stress [137].…”
Section: Inflammatory Mediatorsmentioning
confidence: 75%
“…However, the mechanism of DXZ in ferroptosis and DOX-induced rat cardiomyopathy remains largely unknown. High mobility group box 1 (HMGB1) is a ubiquitous and abundant nucleoprotein that plays a key role in many cardiovascular diseases, such as myocardial ischemia/reperfusion injury, myocardial infarction, and heart failure ( 19 ). HMGB1 was also found to be a critical regulator of ferroptosis in many diseases, such as leukemia ( 20 ), acute liver failure ( 21 ), and diabetic nephropathy ( 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, VEGF is an angiogenic growth factor that can stimulate the proliferation, differentiation, and survival of vascular endothelial cells. Several experiments have indicated that VEGF plays a cardio-protective role in myocardial I/R injury (25,26). Further, most of the host genes of the seven validated circRNAs, such as ATXN10, FAM126A, SBDS, PICALM, and FTO, are closely associated with cell survival, cell proliferation, and cell differentiation (27)(28)(29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%